Stosunki w łódzkiej prasie okresu międzywojennego. Polemika prasowa na łamach łódzkich dzienników na przykładzie „Głosu Polskiego” i koncernu Republiki - Hrycek, Miłosz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
Journalistic polemics started when Poland got its independence back, very often bringing up previous disputes and unresolved issues. One dispute opened up between the editors of the two most important Lodz newspapers at the time – “Głos Polski” and “Ilustrowana Republika”.